The Effectiveness of Digital Marketing Before and After the Covid-19 Pandemic in MSMEs in the Convection Sector - Wibawa, Gian Riksa; Arif, Arif (Dinasti Publisher, 2024)
This study examines the level of effectiveness of digital marketing before and after the Covid-19 pandemic, and to see whether there are changes or not. Using a comparative research methodology, where one variable but uses a large sample or measured at several different times, and the variables analyzed are independent variables. Using snowball sampling and purposive sampling, 100 respondents were selected from among those who received the survey via Google Form. The average pre-pandemic result of 29.65 < 33.34 after the pandemic indicates that there is a difference in the average digital marketing efficacy before and after COVID-19, according to the findings of the study. The results of Sig 0.000 < 0.05 also show a relationship between the level of effectiveness of digital marketing before and after covid-19. In addition, the result of Sig (2-tailed) 0.000 < 0.05 indicates that digital marketing has become more effective after the covid-19 pandemic compared to before the covid-19 pandemic. During the covid-19 pandemic, the level of effectiveness of using digital marketing increased compared to before the pandemic, in line with the results of interviews with business owners engaged in the convection sector, where during the pandemic the level of visits to the content served increased, in addition the level of interaction between potential consumers also increased. during the pandemic.